DEVELOPING INTERCULTURAL COMPETENCE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Fayzullaevna , Tadjieva Mastura (PT. Antis International Publisher, 2024)
This article explores the significance of intercultural competence in teaching of English as a Foreign Language (EFL). The review examines the concept of communicative competence, the understanding of intercultural competence, highlighting the role of cultural knowledge, beliefs, and values in shaping cross-cultural interactions. It underscores the importance of preparing EFL students to navigate unpredictable multicultural situations, rather than solely focusing on familiarity with a single culture. Drawing on a comprehensive analysis of existing literature, the article identifies best practices, theoretical foundations, and practical approaches to integrating intercultural learning into EFL classrooms. The goal is to equip EFL educators with the necessary strategies to foster intercultural understanding and prepare their students for the complexities of a globalized society